Evaluasi Pembelajaran Model CIPP (Context, Input, Process, And Product) Pada Materi Sejarah Asia Selatan - Ipong Jazimah; Septianingsih, Sumiyatun (Universitas Pendidikan Ganesha, 2023)
The ability to carry out evaluations is a basic ability that must be possessed by all educators and prospective educators. In line with the curriculum change to an independent curriculum, the evaluation model must be more active and creative by involving all students' thinking skills, namely cognitive, affective, and psychomotor. This research was conducted to reveal 1) How the CIPP model learning evaluation is used on South Asian history material. 2) What are the results of the CIPP model learning evaluation on South Asian history material? This research was conducted on students of the History Education Study Program, FKIP UMP who were taking the South Asian History course in the even semester 2022/2023 using qualitative research methods. Data sources consist of informants, observation notes, and documents. Data collection was carried out through interviews, observation, and document analysis. Data validity is carried out by data triangulation. Data analysis uses interactive analysis with three stages of analysis, namely data reduction, data presentation, and conclusion. This research resulted in the conclusion that 1) The CIPP model evaluation can be used to evaluate learning of South Asian history material. 2) The products resulting from the CIPP model evaluation of South Asian history material are concept maps and map images of the South Asian region. Keywords: Learning evaluation, CIPP model evaluation, South Asian material